Eagle's syndrome: a piercing matter. Issue 1 (28th November 2018) - Zammit, Matthew; Chircop, Charmaine; Attard, Veronica; D'Anastasi, Melvin
Abstract : We present an unusual case of Eagle's syndrome with bilateral internal carotid artery dissection in a 45-year-old man. Initial symptomatology included ipsilateral headaches and facial sensory symptoms. A right horner's syndrome was present on clinical examination. Radiological imaging revealed an old infarct, with bilateral carotid dissections and bilateral elongated styloid processes consistent with Eagle's syndrome. Despite initiation of secondary prevention with antiplatelet therapy, he had two further ischaemic events. The case highlights the symptomatology and complications of Eagle's syndrome, with its management discussed through a review of similar case reports.